Prospective proof-of-concept observational RESEarch about traditional herbal preparation Treatment for Chronic Obstructive Pulmonary Disease (RESET-COPD-1) - Park, Dasol; Leem, Jungtae; Lee, Beom-Joon; Kim, Kwan-Il; Jung, Hee-Jae (Frontiers in Pharmacology, 2024)
Background: Despite advances in medical science, chronic obstructive pulmonary disease (COPD) continues to impact patients' lives significantly, due to symptom management limitations.Cheongsangboha-tang (CSBHT; Qing Shang Bu Xia Tang) and Hyunggaeyeongyo-tang (HGYGT; Jing Jie Lian Qiao Tang) have been used to treat respiratory diseases, including COPD. However, clinical data supporting their efficacy are lacking. We prospectively observed the response of patients with COPD to CSBHT and HGYGT as adjunctive therapies and assessed the feasibility of future research.: Patients with COPD who were prescribed adjunctive HGYGT or CSBHT according to the COPD clinical practice protocol of Kyung Hee University Korean Medicine Hospital were recruited. Participants visited the hospital every month, for 6 months, to receive herbal preparations according to a Korean Medicine doctor's diagnosis and prescription and outcome evaluations. The primary outcome was the 6-minutes walking test (6-MWT). Secondary outcomes included the pulmonary function test (PFT), COPD Assessment Test (CAT), St. George's Respiratory Questionnaire (SGRQ), and modified Medical Research Council (mMRC) score. Syndrome differentiation, adverse events, and patient adherence were recorded.Results: Thirty-seven patients were initially enrolled and followed up for a mean period of 154.1 days.CSBHT was prescribed to 36 patients, while one patient received either CSBHT or HGYGT, or both, throughout the entire period. During the herbal preparation treatment period, no statistically significant changes were observed in the 6-MWT. The CAT score (mean ± standard deviation) changed from 17.0 ± 5.0 to 12.5 ± 3.6, and the visual analogue scale score for dyspnea changed from 47.5 ± 18.9 to 28.4 ± 18.6 (both statistically significant from visit 5). The coronavirus disease 2019 pandemic precluded the PFT. SGRQ and mMRC scores did not change significantly. During the study period, seven patients dropped out, two experienced mild dyspepsia, and one experienced mild headache. No serious adverse effects were observed.We illustrated the therapeutic potential of CSBHT and provided preliminary clinical data on its efficacy and safety in patients with COPD. Our study highlights the need to derive optimal herbal formulations, which should be administered for an appropriate duration, based on the therapeutic goals for the treatment of COPD.